Reinterpretacja historii w Księgach Kronik. Przypadek króla Manassesa - Kinowski, Krzysztof (Collectanea Theologica, 2020)
The narrative about King Manasseh in the Second Book of Chronicles (33:1-20) is an interesting example of the reinterpretation of historical material found in the Books of Kings. In the first part (2 Chr 33: 1-9) the Chronicler picks up the details of the plot about Manasseh from 2 Kgs 21:1-9 and forms thus its parallel narrative. In the second part (2 Chr 33:10-20) he presents, however, his own material about Manasseh which is absent in the narrative of the Books of Kings (cf. 2 Kgs 21:10-18). In effect, the Books of Chronicles shed different light on the reign of our king. Whereas the Books of Kings present Manasseh as the most impious Judean king, idolater and murderer of the innocent Judahites, causing the fall of his kingdom and its inhabitants who became destined for an exile into Babylon, the Books of Chronicles build up a positive image of Manasseh. Here, he is a sinner who, punished by God, humbled himself before Him and converted, and after his rehabilitation carried out religious reforms and devoted himself to construction works, renewing thus the splendour of the Kingdom of Judah. This alternative tradition about Manasseh harmonises perfectly with the theological message of the Books of Chronicles, since its narrative about Manasseh depicts a well-recognized pattern of the Chronicler, namely sin – punishment – conversion – restoration, which was particularly important to the postexilic community. In Manasseh’s destiny it could reread its own history as punishment for idolatry and unfaithfulness to God, who is willing to forgive its trespasses and restore its lost splendour if it returns to Him. This interrelated link between God’s forgiveness, restoration and conversion is a universal truth, tangible also in today’s addresses of the Holy Scripture.